Analisis Kesehatan Bank Berdasarkan Laporan Tahunan dan Tata Kelola BCA 2022–2024 - Conan Scorpio (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Bank health assessment is fundamental to banking supervision and economic stability. Traditional quantitative approaches using financial ratios have limitations in explaining managerial quality, corporate governance effectiveness, and sustainability commitment. This study aims to analyze bank health qualitatively based on annual reports and corporate governance reports, focusing on risk management quality, Good Corporate Governance implementation, and business sustainability without using financial ratio calculations. The research employs a qualitative descriptive approach with content analysis method on PT Bank Central Asia Tbk for the period 2022–2024. Data were collected from annual reports, GCG reports, and sustainability reports, then analyzed through data reduction, presentation, and conclusion drawing. The findings indicate that the bank demonstrates institutional health characteristics through structured risk management systems, consistent GCG implementation, sustainable business strategies, and adequate transparency. This study concludes that qualitative bank health assessment through annual and governance reports provides a holistic alternative method that captures institutional and managerial dimensions often overlooked in quantitative analysis. Banks with effective risk management, strong corporate governance, and sustainable strategies can be categorized as institutionally healthy banks.